1994
DOI: 10.2307/2393235
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Images and Member Identification

Abstract: We develop a model to explain how images of one's work organization shape the strength of his or her identification with the organization. We focus on two key organizational images: one based on what a member believes is distinctive, central, and enduring about his or her organization and one based on a member's beliefs about what outsiders think about the organization. According to the model, members assess the attractiveness of these images by how well the image preserves the continuity of their self-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

85
3,689
7
158

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,814 publications
(4,092 citation statements)
references
References 55 publications
85
3,689
7
158
Order By: Relevance
“…Thus, a work unit that enables one's spiritual identity can energize the group. Further, others have suggested that belonging to a social group, i.e., to an organization, shapes one's self-concept (Ashforth & Mael, 1989;Dutton et al, 1994;Kramer, 1991;Tajfel & Turner, 1985). Individuals' identities are formed in part by how they believe others view the work unit or organization to which they belong (Dutton & Dukerich, 1991).…”
Section: Inner Lifementioning
confidence: 99%
“…Thus, a work unit that enables one's spiritual identity can energize the group. Further, others have suggested that belonging to a social group, i.e., to an organization, shapes one's self-concept (Ashforth & Mael, 1989;Dutton et al, 1994;Kramer, 1991;Tajfel & Turner, 1985). Individuals' identities are formed in part by how they believe others view the work unit or organization to which they belong (Dutton & Dukerich, 1991).…”
Section: Inner Lifementioning
confidence: 99%
“…Essa associação é interessante porque reforça o argumento de que recursos de tarefa (e.g., autonomia encontrada em cargos acima do operacional) operam como recompensas ao indivíduo e, assim, contribuem à identificação (Eisenberger, Aselage, Sucharski, & Jones, 2004). Cabe destacar ainda que a variável tempo de empresa, ao contrário do afirmado por Dutton et al (1994), não se mostrou associada à identificação. Os Modelos 2, 3 e 4 mostram que a inserção das variáveis suporte da organização, suporte do chefe e dos colegas eleva o poder de explicação comparado às variáveis de controle, de um R 2 Ajustado = 0,05 para 0,33.…”
Section: Análise E Discussão Dos Resultadosunclassified
“…A avaliação de que colegas se preocupam com os valores e sentimentos do indivíduo no trabalho, bem como de que chefe e organização constantemente consideram o seu bem-estar, contribui para criação de imagens de unicidade (Dutton et al, 1994). Assim, a intensidade de suporte social dado pela organização contribui diretamente para identificação com a própria organização.…”
Section: Suporte No Trabalho E Identificação Organizacionalunclassified
See 1 more Smart Citation
“…The first stream of research focuses on the production, projection and embodiment of identity at a macro-organisation level (Gioia, Schultz, & Corley, 2000;Gioia & Thomas, 1996;Parent & Deephouse, 2007). This stream of research typically focuses on employees or former employees of organisations that have intimate knowledge of the intra-organisational environment (Dutton, Dukerich, & Harquail, 1994;Elsbach, 2003;Kreiner & Ashforth, 2004). The second stream of researchdrawn from marketing -explicitly focuses on how an organisation is perceived by its external audience (Bhattacharya & Elsbach, 2002;Elsbach & Bhattacharya, 2001;Lock & Filo, 2012).…”
mentioning
confidence: 99%